2013
DOI: 10.1007/s00586-013-3034-8
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma of the spine: a case involving paraspinal muscle with extensive calcification and the surgical consideration in treatment

Abstract: Introduction Synovial sarcoma is a rare malignant tumor of the spine. This tumor may present as a painless mass of the spine or slowly enlarge, causing pain or neurologic deficits. As it is difficult to differentiate this lesion from other soft tissue tumors, synovial sarcoma requires histologic confirmation for definite diagnosis. Thus, the treatment strategy is often planned in the final step depending on the pathologic results. Despite its rare incidence, a few cases of primary or metastatic synovial sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…2,19 Spinal SS is a rare entity also in the adult population and up to now, only 18 adult patients have been documented as case reports in the literature. 5,6 Wide surgical excision with negative surgical margins followed by chemotherapy and/or radiotherapy is the currently recommended treatment in the adult population. To preserve the adjacent structures and limit the neurologic impairment, marginal resection was performed in most of these reported patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 Spinal SS is a rare entity also in the adult population and up to now, only 18 adult patients have been documented as case reports in the literature. 5,6 Wide surgical excision with negative surgical margins followed by chemotherapy and/or radiotherapy is the currently recommended treatment in the adult population. To preserve the adjacent structures and limit the neurologic impairment, marginal resection was performed in most of these reported patients.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the reported cases are adults and majority of their tumors were located outside the duramater. 5,6 Here, we present a case of primary intradural extramedullary SS in the cervicothoracic region. To our knowledge, this is the youngest case of intradural extramedullary spinal SS in the literature.…”
mentioning
confidence: 99%
“…En bloc resection is important in spinal tumours to minimize the tumour residue. Kim et al [ 6 ] reported a C2 SS removed with negative margins, and Cao et al [ 33 ] reported another case who underwent a T7 en bloc resection. Both patients survived without recurrence in their 2- and 1-year follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It can arise from the osseous and paravertebral soft tissues and even metastasize from other sites [ 4 , 5 ]. With the enlargement of a SS, the mass can result in pain and other symptoms [ 6 , 7 ]. Spinal instability, vertebral collapse and neurologic deficits may occur from the destruction of vertebrae structure and compression of nerve roots and the spinal cord [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors describe a case of a 29-year-old male with a non-metastatic paraspinal muscle calcified synovial sarcoma [10]. Surgical resection achieved adequate margins (complete excision) and the patient received adjuvant external beam radiotherapy (60 Gy).…”
mentioning
confidence: 99%